Impact of Liminality in Organic Agricultural Tourism on Well-Being: The Role of Memorable Tourism Experiences as a Mediating Variable - Dan Wang; Ching-Cheng Shen (Agriculture)
Organic agricultural tourism integrates organic, toxin-free natural environments with agricultural industry and cultural lifestyles, creating a liminal space and experience away from everyday life. This study explores how this environment influences tourists’ memorable tourism experiences and subjective well-being. The research employed a questionnaire survey targeting tourists engaged in organic agricultural tourism in the Hualien and Taitung regions of Taiwan. This study used convenience sampling and collected a total of 440 valid questionnaires from 1 October to 30 December 2023. SPSS and PLS-SEM were employed as the analysis tools. The findings are as follows: 1. Developed scales for organic agricultural tourism liminal space, liminal experience, liminal place, and liminal benefits, validating their reliability and validity. 2. Verified that liminality has a significant positive impact on memorable tourism experiences, which in turn positively affect subjective well-being. 3. Identified and validated the mediating role of memorable tourism experiences in the relationship between liminality in organic agricultural tourism and subjective well-being. 4. Found that liminal experience has the most significant impact on memorable tourism experiences, followed by liminal benefits, highlighting the critical role of liminal experience in tourists gaining benefits from liminal spaces. 5. Expanded the application of liminality theory in tourism-related research, providing theoretical support for how organic agricultural tourism can deepen tourists’ memorable tourism experiences and enhance their subjective well-being through liminality. This study is innovative both in its theme and theoretical contributions, offering significant academic and practical implications for the field.